Optimasi Produksi Roti Menggunakan Algoritma Affine Scaling Di Olivia Bakery - azilah, nur; Murni, Dewi (UNIVERSITAS NEGERI PADANG, 2024)
Olivia Bakery is a business specializing in the production of sweet bread in various flavors. Currently, the bakery faces challenges in production planning, as it struggles to determine the optimal number of breads to produce for each variant based on the availability of raw materials. The objective of this study is to formulate a mathematical model that incorporates the constraints of raw material availability, production time, and market demand to determine the optimal production quantities and maximize profits. This problem is addressed using an optimization approach with the Affine Scaling Algorithm. The research is categorized as applied research and utilizes both primary and secondary data obtained through observation and documentation. The results of the analysis show that the use of the Affine Scaling Algorithm generates a profit of Rp 635,117.00, compared to the average normal profit of approximately Rp 497,888.00. Therefore, this method proves to be more effective in increasing the company's profitability.